2007
DOI: 10.1044/1092-4388(2007/071)
|View full text |Cite
|
Sign up to set email alerts
|

Receptive and Expressive Prosodic Ability in Children With High-Functioning Autism

Abstract: Purpose This study aimed to identify the nature and extent of receptive and expressive prosodic deficits in children with high-functioning autism (HFA). Method Thirty-one children with HFA, 72 typically developing controls matched on verbal mental age, and 33 adults with normal speech completed the prosody assessment procedure, Profiling Elements of Prosodic Systems in Children. Results Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
265
5
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(315 citation statements)
references
References 28 publications
(25 reference statements)
26
265
5
7
Order By: Relevance
“…They include poorer performance in ASD compared to TD on the Focus task (Peppé et al, 2007), and a significant difference on a lexical stress task (Paul et al, 2005; as noted, the latter was not a vocal imitation task and may thus make cognitive and verbal demands that differ from those made by our lexical stress task). The results from the Paul et al (2005) study are difficult to relate to the present study because no group matching information was provided, tasks involved reading text aloud, the age range was broad and older ( M age for ASD = 16.8, SD = 6.6), and certain tasks had serious ceiling effects.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…They include poorer performance in ASD compared to TD on the Focus task (Peppé et al, 2007), and a significant difference on a lexical stress task (Paul et al, 2005; as noted, the latter was not a vocal imitation task and may thus make cognitive and verbal demands that differ from those made by our lexical stress task). The results from the Paul et al (2005) study are difficult to relate to the present study because no group matching information was provided, tasks involved reading text aloud, the age range was broad and older ( M age for ASD = 16.8, SD = 6.6), and certain tasks had serious ceiling effects.…”
Section: Methodsmentioning
confidence: 83%
“…Prosody characteristics noted for persons with ASD have included monotonous speech as well as sing-song speech, aberrant stress, atypical pitch patterns, abnormalities of rate and volume of speech, and problematic quality of voice (e.g., Baltaxe, 1981; Baltaxe, Simmons, & Zee, 1984; Shriberg, Paul, McSweeny, Klin, Cohen, & Volkmar, 2001). Findings obtained with the Profiling Elements of Prosodic Systems-Children instrument (PEPS-C; Peppé & McCann, 2003), a computerized battery of tests consisting of decontextualized tasks that span the linguistic-pragmatic-affective continuum, include poorer performance by children with ASD compared to typically developing (TD) children, particularly on affective and pragmatic prosody tasks (Peppé, McCann, Gibbon, O'Hare, & Rutherford, 2007; McCann, Peppé, Gibbon, O’Hare, & Rutherford, 2007). …”
mentioning
confidence: 99%
“…Specifically, some research groups reported that individuals with ASD exhibited deficits in the comprehension of grammatical cues of word stress (Paul, Augustyn, Klin, & Volkmar, 2005a;Peppé et al, 2007), whereas others have not (Chevallier, Noveck, Happé, & Wilson, 2009;Crossman et al, 2010;Järvinen-Pasley, Peppé, King-Smith, & Heaton, 2008a). A similar pattern of inconsistencies in the results is evident in studies exploring the ability to use stress to perceive phrase structures in individuals with ASD.…”
Section: Introductionmentioning
confidence: 67%
“…A similar pattern of inconsistencies in the results is evident in studies exploring the ability to use stress to perceive phrase structures in individuals with ASD. Specifically, some studies have reported evidence for impaired performance in individuals with ASD relative to controls (Diehl, Benneton, Watson, Gunlogson & McDonough, 2008;Jarvinen-Pasley et al, 2008a), while other studies have not found significant group differences on performance (Paul et al, 2005a;Peppé et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation